Firm integration strategies and imperfect labour markets. (21st July 2016) - Egger, Hartmut; Egger, Peter; Seidel, Tobias
Abstract: This paper introduces labour market imperfections into a three‐country model to study the determinants of firm integration strategies in an open economy. Accounting simultaneously for the decision upon in‐house production versus international outsourcing and the decision upon exporting versus horizontal foreign investment, the analysis points to a crucial role of labour market frictions for the interaction of vertical and horizontal aspects of firm integration strategies in a general equilibrium environment. Beyond that, the analysis sheds light on the consequences of integrating developing countries into the global market, thereby pointing to hitherto unexplored effects arising from adjustments of firm integration strategies. In a welfare analysis, we show that the existence of gains from trade crucially depends on whether firm integration strategies are endogenous or not. Résumé: Stratégies d'intégration des firmes et marchés du travail imparfaits . Ce texte injecte des imperfections dans les marchés du travail dans un modèle à trois pays pour étudier les déterminants des stratégies d'intégration des firmes dans une économie ouverte. Tenant compte simultanément de la décision de produire à l'interne ou de faire de la sous‐traitance internationale, et de la décision d'exporter ou d'investir horizontalement à l'étranger, l'analyse souligne le rôle important des frictions sur le marché du travail sur l'interaction entre les aspects verticaux et horizontaux des stratégies d'intégration des firmes dans un environnement d'équilibre général. L'analyse jette aussi un peu de lumière sur les conséquences qu'il y à intégrer des pays en voie de développement dans leurs stratégies. En termes d'analyses de bien‐être, on montre que l'existence de gains du commerce dépend du fait que les stratégies d'intégration sont endogènes ou non.